2007
DOI: 10.1186/1478-7547-5-9
|View full text |Cite
|
Sign up to set email alerts
|

The economic burden of treating neonates in Intensive Care Units (ICUs) in Greece

Abstract: BackgroundIn a period when a public-private mix in Greece is under consideration and hospital budgets become restrained, economic assessment is important for rational decision making. The study aimed to estimate the hospitalization cost of neonates admitted to the ICUs and demonstrate discrepancies with reimbursement.MethodsChosen methodology was based on the selection of medical records of all NICUs and intermediate care admissions within February to April 2004. Neonates (n = 99) were classified according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 16 publications
4
11
1
Order By: Relevance
“…This study also demonstrated the increase in mean cost per admission with level of care and degree of prematurity. This inverse relationship is compatible with literature where studies have shown that increasing prematurity equates to intense resource utilization that translates into higher cost (35, 14, 15). Although mean cost per day for a preterm infant increased with the level of care and prematurity in this study, increments in cost per day between levels of care and preterm categories were not pronounced (5% - 10%).…”
Section: Discussionsupporting
confidence: 90%
“…This study also demonstrated the increase in mean cost per admission with level of care and degree of prematurity. This inverse relationship is compatible with literature where studies have shown that increasing prematurity equates to intense resource utilization that translates into higher cost (35, 14, 15). Although mean cost per day for a preterm infant increased with the level of care and prematurity in this study, increments in cost per day between levels of care and preterm categories were not pronounced (5% - 10%).…”
Section: Discussionsupporting
confidence: 90%
“…3 The ability to coordinate sucking, swallowing, and breathing is evidence of neurodevelopmental maturation. 26 In today's managed care environment, most preterm infants are discharged within 24 to 48 hours of achieving decision-making process. 25 The question that the feeding specialist may ask is: are oral feedings appropriate from a neurodevelopmental, physiological, and organizational perspective for this infant?…”
Section: Invented Casesmentioning
confidence: 99%
“…20 Another research conducted in Greece in 2004 verifi ed that the mean cost for the government with newborns weighing between 1001 and 1500g in intensive neonatal care public units was US$10,438. 12 It is not our intention to debate the need of these units, but rather, what could be done at lower costs to avoid the excessive demand of these services. Apart from the higher fi nancial cost, there are intangible costs, as low weight babies present higher risk of avoidable neonatal death, according to the classifi cation of Malta et al, 17 related to failures in prenatal assistance and to the handling of childbirth and of the neonatal period.…”
Section: Discussionmentioning
confidence: 99%
“…12,20 In 2001, a study carried out in the United States compared the mean cost of the hospitalization of preterm/low birth weight children with normal weight newborns, which corresponded to US$15,800 and US$600, respectively. 20 Another research conducted in Greece in 2004 verifi ed that the mean cost for the government with newborns weighing between 1001 and 1500g in intensive neonatal care public units was US$10,438.…”
Section: Discussionmentioning
confidence: 99%